Emotionally reflexive labour in end-of-life communication. (December 2021) - Olson, Rebecca E.; Smith, Alexandra; Good, Phillip; Neate, Emily; Hughes, Cody; Hardy, Janet
Abstract: Within palliative care, clear and open communication about death is encouraged. Euphemisms are discouraged as threats to promoting clear understanding of the prognosis; to opening communication about what a good death means to individual patients and families; and to fostering collaborative planning aimed at achieving this 'good death'. Principles of patient-centred and culturally competent care, however, which reflect trends of individualisation, plurality and multiculturalism that are characteristic of late modernity, encourage respect for and support of patients' and families' preferences. These may include wishes to avoid open communication, preferences for euphemisms, and definitions of a 'good death' that vary from the practitioner's, and within families. The aim of this study was to examine how physicians navigate these competing priorities. Analysis is based on interviews with 23 doctors, ranging in experience from medical students through to senior palliative care specialists, and eight recorded observations of palliative care multidisciplinary team meetings with 52 clinicians collected in 2017 at two hospitals in one Australian metropolitan area. Findings show that synonyms familiar to clinicians are often used to communicate prognoses in multidisciplinary meetings. In communication with patients and families, doctors rely on emotional and cultural cues to decipher the preferred terminology and response. Drawing on a late modern re-imagination of emotion management, we conceptualise the work performed in this context as emotionally reflexive labour. These findings suggest that blanket protocols for direct communication overlook the complexity of end-of-life communication in an era where a 'good death' is understood to be culturally relative. Highlights: Definitions of dying well in late modernity are individually and culturally relative. Doctors perform emotionally reflexive labour to tailor communication. In interactions with other clinicians, placeholders for death are widely used. Blanket protocols for direct end-of-life communication may be inappropriate.